Naturally-derived protein extract from Gryllus bimaculatus improves antioxidant properties and promotes osteogenic differentiation of hBMSCs. - Keya Ganguly (Public Library of Science (PLoS), 2021)
Naturally-derived proteins or peptides are promising biopolymers for tissue engineering applications owing to their health-promoting activity. Herein, we extracted proteins (~90%) from two-spotted cricket (Gryllus bimaculatus) and evaluated their osteoinductive potential in human bone marrow-derived mesenchymal stem cells (hBMSCs) under in vitro conditions. The extracted protein isolate was analyzed for the amino acid composition and the mass distribution of the constituent peptide fraction. Fourier transform infrared (FTIR) spectroscopy was used to determine the presence of biologically significant functional groups. The cricket protein isolate (CPI) exhibited characteristic protein peaks in the FTIR spectrum. Notably, an enhanced cell viability was observed in the presence of the extracted proteins, showing their biocompatibility. The CPI also exhibited antioxidant properties in a concentration-dependent manner. More significant mineralization was observed in the CPI-treated cells than in the control, suggesting their osteoinductive potential. The upregulation of the osteogenic marker genes (Runx2, ALP, OCN, and BSP) in CPI treated media compared with the control supports their osteoinductive nature. Therefore, cricket-derived protein isolates could be used as functional protein isolate for tissue engineering applications, especially for bone regeneration.